Tagging in antiquity: Pompeian graffiti between individuality and convention - Lohmann, Polly (Graffity, street art & urban creativity scientific journal, 2020)
The article is based on a paper presented at the international conference “Tag. Name Writing in Public Space” (Berlin 2017) which brought together graffiti specialists and artists. Therefore the contribution aimed at a broader, interdisciplinary audience. The present article analyses ancient “tags”, which form the largest portion of the graffiti found at the site of Pompeii, and discusses methodological problems in dealing with this epigraphic record. Due to the characteristics of Roman onomastics, it is hardly possible to trace individuals in the Pompeian graffiti. The focus therefore is on those rare examples where we can distinguish individuals by attributes or additional names (such as family names / gentilicia) indicated. The article shows that while the basic human desire to leave one’s (individual) mark was omnipresent on the one hand, the ancient tags on the other hand where quite uniform and thereby almost de-individualised.